Treatment of pharmaceutical wastewater using mesophilic UASB and hybrid UASB reactors - Herumurti, W.; Isa, M.H.; Kutty, S.R.M. (2008)
Biological treatment of pharmaceutical wastewater was performed using upflow anaerobic sludge blanket (UASB) and hybrid upflow anaerobic sludge blanket (hybrid UASB) reactors. Pre-treatments were not used in this study. Wastewater was taken from pharmaceutical factory that produced non-penicillin product. UASB and hybrid UASB reactors were evaluated under mesophilic (35±1°C) operating condition. Three hydraulic retention times (HRT) i.e. 5 days, 4 days, and 3 days were used for all reactors. The reactors were seeded with sludge from aerobic treatment. The chemical oxygen demand (COD) of wastewater was 458-2,217 mg/L. COD removal efficiencies were approximately 93 % and 94% in UASB and hybrid UASB reactors, respectively at HRT of 5 days. The highest methane production was achieved by hybrid UASB reactor at HRT of 4 days. Analysis of variance (ANOVA) performed on the results showed that, at 5% level of significance; the COD removal was significantly affected by type of reactors and hydraulic retention time.